Non-chemotactic Dictyostelium discoideum mutants with altered cGMP signal transduction (The Rockefeller University Press, 1993)
Folic acid and cAMP are chemoattractants in Dictyostelium discoideum, which bind to different surface receptors. The signal is transduced from the receptors via different G proteins into a common pathway which includes guanylyl cyclase and acto-myosin. To investigate this common pathway, ten mutants which do not react chemotactically to both cAMP and folic acid were isolated with a simple new chemotactic assay. Genetic analysis shows that one of these mutants (KI-10) was dominant; the other nine mutants were recessive, and comprise nine complementation groups. In wild-type cells, the chemoattractants activate adenylyl cyclase, phospholipase C, and guanylyl cyclase in a transient manner. In mutant cells the formation of cAMP and IP3 were generally normal, whereas the cGMP response was altered in most of the ten mutants. Particularly, mutant KI-8 has strongly reduced basal guanylyl cyclase activity; the enzyme is present in mutant KI-10, but can not be activated by cAMP or folic acid. The cGMP response of five other mutants is altered in either magnitude, dose dependency, or kinetics. These observations suggest that the second messenger cGMP plays a key role in chemotaxis in Dictyostelium.